Influence of Socioeconomic Status on Knowledge of Obesity and Diabetes among Adolescents in Chennai, South India - Pranati Panuganti; T.S. Mehreen; Ranjit Mohan Anjana; Viswanathan Mohan; E. Mayer-Davis; Harish Ranjani (MDPI AG, 2017)
The Obesity Reduction and Awareness of Non-communicable disease through Group Education (ORANGE) Phase II program, is a school-based intervention aimed at healthy lifestyle practices for sixth and seventh grade adolescents (n = 2345) attending private (n = 1811) and government (n = 534) schools in Chennai. The objectives of this paper are (a) to describe the intervention activities and their outcomes qualitatively and (b) to report changes in body mass index (BMI) of the intervention group participants. This intervention strategy used a teacher-peer-training model in each school for long-term sustainability of the lessons learned from this program. During each intervention session, teachers led a classroom discussion on the health topic of interest, and peers facilitated small-group learning activities. Anthropometric measurements of participants were assessed pre- and post-intervention. We found government school students perceived hygienic actions (e.g., drinking clean water, taking baths daily) as healthy habits for preventing diabetes, whereas private school students associated an expensive lifestyle (e.g., eating at restaurants, riding a car) with diabetes prevention. Overall, the mean post-intervention BMI (18.3 kg/m2) was in the normal range compared to the pre-intervention BMI (17.7 kg/m2) (p < 0.0001). These results suggest that future interventions should be tailored for adolescents from different socio-economic groups while acknowledging their varied perceptions.